Capitalism and rights: An essay toward fine tuning the moral foundations of the free society - Pilon, Roger (Journal of business ethics, 1982)
The moral foundations of the free society are not epitomized by democratic decisions about costs and benefits, as Michael Novak recently argued in The American Vision: An Essay on the Future of Democratic Capitalism. Nor is equality of opportunity, insured through government measures that prohibit private discrimination, a component of the liberty that characterizes the free society, as Milton and Rose Friedman recently argued in their Free To Choose. Rather, it is the theory of rights — which is the theory of private property, broadly understood — that underpins and epitomizes the free society, justifying the capitalist economic order in the process. For that theory describes our basic moral and legal relationships, and shows as well that capitalism, unlike socialism, is a fundamentally moral system.